2019
DOI: 10.1155/2019/5676159
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Dispersion and Aggregation of Gold Nanorod in Aptamer-Mediated Gestational Hypertension Analysis

Abstract: Gestational hypertension is one of the complicated disorders during pregnancy; it causes the significant risks, such as placental abruption, neonatal deaths, and maternal deaths. Hypertension is also responsible for the metabolic and cardiovascular issues to the mother after the years of pregnancy. Identifying and treating gestational hypertension during pregnancy by a suitable biomarker is mandatory for the healthy mother and foetus development. Cortisol has been found as a steroid hormone that is secreted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…All the complications were diagnosed by the obstetrician in the following criteria. Gestational hypertension: systolic blood pressure >140 mmHg (1 mmHg = 0.133 kPa) or diastolic blood pressure >90 mmHg after 20 weeks of gestation, without proteinuria [9] . GDM: fasting plasma glucose ≥5.1 mmol/L, or have a 75-g oral glucose tolerance test, after 1 h ≥10.0 mmol/L or after 2 h ≥8.5 mmol/L [10] .…”
Section: Methodsmentioning
confidence: 99%
“…All the complications were diagnosed by the obstetrician in the following criteria. Gestational hypertension: systolic blood pressure >140 mmHg (1 mmHg = 0.133 kPa) or diastolic blood pressure >90 mmHg after 20 weeks of gestation, without proteinuria [9] . GDM: fasting plasma glucose ≥5.1 mmol/L, or have a 75-g oral glucose tolerance test, after 1 h ≥10.0 mmol/L or after 2 h ≥8.5 mmol/L [10] .…”
Section: Methodsmentioning
confidence: 99%
“…The developed aptasensor allowed for the detection of physiological concentrations of cortisol (from 150 to 600 nM). A similar aptasensor was developed by X. Bao et al [ 44 ]. However, it was much less sensitive, and the limit of detection was only 690 μM (0.25 mg/mL).…”
Section: Aptasensors For Biomarker Detectionmentioning
confidence: 99%
“…Several methods that include passive adsorption and covalent bonding are used to produce a stable conjugation. Although gold nanoparticle has its own unique characteristics, such as rich in surface chemistry and low toxicity, it is not often used in the conjugation process due to it is highly costly to produce a final product [12][13][14]. Taken together, it can be concluded that conjugation method is safe and easy to use when combining with different materials.…”
Section: Introductionmentioning
confidence: 99%